Research on the mechanism of the anti-myocardial infarction effect of the Qiliqiangxin capsule on heart failure rats via nontargeted metabolomics and lipidomics - Kuangyi Liu; Yanting Xiong; Yingli Fan; Shunhui Li; Lijuan Wu; Hui Chen; Xiaomin Wang (BMC Cardiovascular Disorders)
Abstract Background Qi Li Qiang Xin (QLQX) capsule has a solid theoretical basis and clinical efficacy in the treatment of chronic heart failure; however, the underlying mechanisms remain obscure. This study was designed to determine the effect of the QLQX on the treatment of heart failure and delineate the underlying mechanisms via a nontargeted metabolomics and lipidomics approach. Methods A rat model of heart failure after myocardial infarction (MI) was established via permanent ligation of the anterior descending branch of the left coronary artery. The rats were then randomly divided into the SHAM group, the MI group, the QLQX group (1.3 g/kg/day), and the VAL (valsartan) group (80 mg/kg/day). Cardiac function was measured via echocardiography. The levels of serum NT-proBNP and hs-cTn-I were detected via ELISA. H&E staining and Masson’s trichrome staining were used to observe cardiac morphology and myocardial fibrosis. Using the UPLC-QTOF/MS method, metabolomics and lipidomics analyses were performed on the plasma of the rats in each group to identify biomarkers and potential amino acid and lipid therapy mechanisms for heart failure after QLQX administration in rats with heart failure. Results QLQX capsule improved the heart f unction of rats with heart failure after myocardial infarction by increasing the LVEF and LVFS, decreasing the LVIDd and LVIDs. QLQX capsule reduce the levels of NT-proBNP and hs-cTn-I, which are markers of heart failure, and improve the myocardial infarction area and degree of myocardial fibrosis. In addition, in the metabolomics analysis, a total of 17 plasma metabolites were significantly different between heart failure rats and normal rats, all of which recovered significantly after QLQX treatment. These metabolites mainly participate in the biosynthesis of unsaturated fatty acids; valine, leucine and isoleucine biosynthesis; phenylalanine, tyrosine and tryptophan biosynthesis; and glycerophospholipid metabolism. Lipid analysis revealed that FA18:2, FA18:3, FA20:5, and FA22:6 in the QLQX group were significantly altered (P < 0.01). The peak area contents of FA18:2, FA18:3, FA20:5, and FA22:6 in the sham surgery group and model group also significantly decreased (P < 0.05). Conclusion This study elucidates the therapeutic effect of QLQX on heart failure rats and elucidates its potential mechanisms, which are related mainly to the regulation of amino acid and lipid metabolism in heart failure rats through metabolomics and lipidomics experiments.